PERBEDAAN PEMBERIAN JAMBU BIJI MERAH (PSIDIUM GUAJAVA) DAN BIT (BETA VULGARIS) TERHADAP KADAR HEMOGLOBIN IBU HAMIL - Bunga Tiara Carolin; Siti Syamsiah; Deresiyana Deresiyana (LPPM Universitas Abdurrab, 2021)
Anemia is a problem of MMR in Indonesia. based on the global prevention of Anemia, the prevalence of anemia in pregnant women is 28.3%. The anemia rate in Rangkap Jaya Health Center is 64.3%. Anemia occurs due to physiological changes and is aggravated by malnutrition. Efforts that can be done so that pregnant women do not experience anemia are consumption of Fe tablets, improve diet and add vitamin C-rich food substances such as those found in red guava fruit and beets. This study aims to determine the differences in the administration of red guava fruit juice (Psidium Guajava) and beet juice (Beta Vulgaris) to hemoglobin levels in anemic pregnant women at Puskesmas Rangkapan Jaya Depok. Methodology this study uses a Quasy Experiment design with a Two Group Pretest Posttest Design. The population in this study are all trimester III pregnant women. The samples of this study arev30 people with the intervention of red guava juice and beet juice. Given for 14 days which are 250 cc. The sampling technique used is purposive sampling. Results: That there are differences in the provision of red guava juice and beet juice on hemoglobin levels in pregnant women. With the average value before and after administration of red guava fruit juice is 8.4 g / dl to 11.5 g / dl and the average value before and after beet juice is 8.5 g / dl to 10.2 g / dl. p-value of 0.001. The conclusions is Red guava juice is more effective against changes in hemoglobin levels.